KEMAMPUAN MENJELASKAN DAN MERANCANG PENGEMBANGAN PEMBELAJARAN BILANGAN DESIMAL DAN PERSEN PADA SISWA KELAS IV SD NEGERI 1 SIDETAPA KECAMATAN BANJAR, KABUPATEN BULELENG - Dewi, Putu Rina; Gusti Ngurah Arya Yudaparmita; I Nyoman Pancaria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is survey research intended to find out and describe the development of learning decimal numbers and percents in class IV of SD Negeri 1 Sidetapa, Buleleng district. This research was conducted in class IV at SD Negeri 1 Sidetapa with a total of 26 students. Data analysis uses parameter estimation to see the development of learning decimal numbers and percents. In this case, research regarding designing the development of learning decimal numbers and percents uses survey research which aims to deepen the development of students at SD Negeri 1 Sidetapa, especially class IV, regarding this material. The results of the research show that in general the ability to understand decimal numbers in class IV students at SD Negeri 1 Sidetapa needs to be improved further. Because there are still many students who don't really understand the information and get grades that are below average. The low level of students' understanding of decimal numbers and percentages can be seen from the results of the students' work in the attached picture and in the list of values listed. Most students have not been able to solve problems or carry out operations of adding decimals and percents well. There are still many students who focus on ordinary addition and do not use the concept of decimal numbers and percent. It is hoped that teaching staff will design learning well, whether from learning media or other things that can support learning well and can be accepted by students correctly and without misconceptions. There are only 27% of 100 students in the high category. There are only 35% of students in the medium category. And students in the low category reached 38%. Where in this case students in the low category in mathematics are quite high at SD Negeri 1 Sidetapa, especially in class IV.